Ways of historical development of indigenous adjectives - Bayalieva, G.Zh.; Saryshova, K.S. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
Modern linguistics undergoes new trends of development as a new approach to every linguistic phenomenon is needed. The present research paper is devoted to the examination of the Kazakh language by way of a comparative analysis with the written language, which can be discovered in medieval monuments of the Turkic world, to find out the cognitive features of the language. The history of the adjectives formation shows that, in spite of the absence of any important semantically and categorically peculiarities between adjectives in the Turkic monuments and in the modern Kazakh language, there are phonetic peculiarities. The use of adjectives has morphed through time and depicts changes in form and semantics. This is more so seen in the analysis of indigenous adjectives. An example is a cross-linguistic comparison of the Turkic languages, which identifies two main characteristics of these adjectives, to which this article focuses. Moreover, the research insists that adjectives of modern Kazakh have specific cognitive properties that are formed in the dynamics of the interaction with internal, social, and natural conditions. The main adjectives are divided into such features as color, evaluative and qualitative properties, size and space dimension.